Write in style a guide to good English - Palmer, Richard (E & FN Spon, 1993)
Write in Style is aimed at all for whom clarity and accuracy of expression are important skills. All the main styles and grammaticalrules are covered, their sense axplained and vivid examples given of how not to write. Plenty of sound and meticulous advice is offered in a friendly and enthusiastic toneand a large part of the book covers specific types of writing, from essays and articles to minutes and reportage. The many illustrations, examples and exercises throughout help the reader put into practice the techniques and skillds the book explores.